Blue Economy and Local Wisdom: Synergy of Pecalang Segara in the Indonesia Sustainable Oceans Program (ISOP) Implementation - Dewi, Ni Nyoman Clara Listya; Zia’ulhaq As Shidqi; Tunjung Wijanarka (Journal of World Trade Studies, 2024)
This study aims to discuss Indonesia’s role in optimizing the implementation of the blue economy through (Indonesia Sustainable Oceans Program) ISOP by focusing on synergy based on local wisdom. A literature review is accomplished to gather evidence of the genuine efforts that Indonesia has made through ISOP and the immediate involvement of Pecalang in conserving Bali’s Ocean. The blue economy concept provides an opportunity to increase public understanding of the importance of keeping the sea sustainable. On the other hand, the government is expected to provide support through implementing policies for optimal management of the sea and surrounding resources. This role is essential because Indonesia is an archipelagic country that fully utilizes the sea as its primary resource. According to Ministry of Environment and Forestry of Indonesia, at least 14 million tons of plastic still end up in the Indonesian ocean every year, thus it needs a different approach to tackle this issue. A local wisdom-based approach can be a more effective and progressive conservation measure. The author uses a case study on Pecalang Segara as a local protective agent for Bali’s marine conservation. Through a qualitative study with descriptive analysis, the authors conclude that the immediate involvement of Pecalang Segara as a local community in implementing ISOP can encourage the formation of a more effective guidance scheme in implementing sustainability from the blue economy concept.